PENGUATAN CALON GURU SEBAGAI PENELITI DI JURUSAN PENDIDIKAN AGAMA ISLAM FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA - Suwadi Suwadi (Jurnal Pendidikan Agama Islam, 2013)
This article is the result of individual study aims to present a clear description of the final project completion governance/skripsi at the Department of Islamic Education. Governance is meant strengthening step for prospective teachers as researchers reach the majors profile. Setting the location of PAI students who are completing the final task in the 2012/2013 academic year. After the participant observation, in-depth interviews and qualitative analysis, it is concluded as follows. First, the completion of the final project pursued through the five stages (a ) administrative requirements, (b) seminar proposals, (c) writing, (d) munaqasyah, and (e) evaluation. Second, the strengthening of prospective teachers as researchers pursued through strengthening measures (a) the implementation of governance through independent study, (b) guiding thesis supervisor through the establishment of appropriate science and expertise, (c) the selection of a theme/ title by giving students the opportunity to submit theme studies according to their interests, (d) institutional support/ reference in the form of optimizing the use of instruments, distribution of handbooks, guidance card control, provision of literature, (e) peer support group through a jigsaw.